(untitled) (Хабаршы. Психология және социология сериясы, 2025)
The study examines the relationship between psychological well-being and self-regulation mechanisms, which are viewed as key internal regulatory processes ensuring emotional balance, cognitive stability, and the ability to adapt to changing sociocultural conditions. The relevance of this topic arises from the growing scientific interest in the structure of subjective well-being and in the psychological mechanisms that maintain the integrity of an individual’s inner state and prevent emotional-personal maladaptation. The aim of the research was to identify the influence of core self-regulation components - planning, modeling, programming, result evaluation, and behavioral flexibility - on indicators of subjective and psychological well-being. This approach is grounded in the understanding of self-regulation as a multilevel dynamic system that determines the quality of personal adaptation and the degree of life satisfaction. The findings confirmed a stable positive relationship between self-regulation levels and the expression of well-being components. It was shown that well-developed regulatory skills strengthen autonomy, personal growth, self-acceptance, and the ability to build constructive social relationships. The value of the study lies in clarifying the role of self-regulation as a psychological resource that supports emotional stability. The results can be used in the development of preventive programs targeting emotional difficulties, as well as in psychological interventions aimed at enhancing subjective well-being and improving self-regulatory skills. Keywords: personality, self-regulation, psychological well-being, subjective satisfaction, mental health, autonomy.